Wkład Władysława Górskiego w prace Zespołu Prawa Cywilnego Materialnego Komisji Kodyfikacyjnej PRL - Dolata, Tomasz (Lʹvìvsʹkij nacìonalʹnij unìversitet ìmenì Ìvana Franka, 2021)
The aim of the article is to describe the influence of an outstanding scientist Władysław Górski on the work of the Substantive Civil Law Team of the Codification Commission of the Polish People’s Republic. The author presents the concepts of this scientist presented to the Codification Committee during the work on the adoption of the Polish Civil Code of 1964 and the course of the work of the Team in this regard. As a result, the author comes to the conclusion that the merit of W. Górski was the introduction of a storage contract to the Civil Code. Earlier, this contract was not included in the draft of the Civil Code at all. Another successful conclusion of the scientist was the change of the term “expedition” contract into “forwarding”. In terms of the structure of the contract of carriage, W. Górski proposed division of the contract of carriage into: general provisions, the carriage of passengers and the carriage of goods was approved. As for the juridical shape of the regulations prepared by W. Górski, it should be noted that the storage and forwarding contracts have been accepted by the Team, but the draft of transport contract has not been approved. The change of the systematics of the draft code in terms of the order of contracts also turned out to be fulfilled by W. Górski. The scientist argued that the contract of carriage should be settled before the forwarding contract. The author’s findings are based on the analysis of archival sources, i.e., documentation contained in the resources of the Archives of New Files in Warsaw.
Keywords: kodeks cywilny 1964 r.; Komisja Kodyfikacyjna PRL; Zespół Prawa Cywilnego Materialnego; Górski, Władysław (1917-2015); umowa spedycji; umowa przewozu; umowa składu; civìlʹnij kodeks 1964 r.; Kodifìkacìjna komìsìâ PNR; Grupacivìlʹnogo materìalʹnogo prava; ekspedicìjnij kontrakt; kontrakt perevezennâ; kontrakt skladu